The association between SARS-CoV-2 vaccines and transverse myelitis: A review. (July 2022) - Naeem, Fatima Naz; Hasan, Syeda Fatima Saba; Ram, Muskaan Doulat; Waseem, Summaiyya; Ahmed, Syed Hassan; Shaikh, Taha Gul
Abstract: In late 2019, the emergence of a new viral strain, later referred to as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) took the shape of a global pandemic, affecting millions of lives and deteriorating economies around the globe. Vaccines were developed at an exceptional rate to combat the viral desolation, all of them being rolled out once they displayed sufficient safety and efficacy. However, assorted adverse events came into attention, one of them being Transverse Myelitis (TM), an infrequent, immune-mediated, focal disease of the spinal cord. This disorder can lead to severe neurological complications including autonomic, sensory, and motor deficits. The literature aims to shed light on TM and its various etiologies, specifically in line with the vaccine, and a comprehensive treatment plan. Discussing and reducing the number of vaccines related adverse events can help succor in bringing down the vaccine hesitancy and ultimately combatting the pandemic. Highlights: The COVID-19 global vaccination program achieved significant results in reducing mortality. Transverse myelitis (TM) is an immune-mediated, focal disease of the spinal cord that may involve one or more levels. According to Vaccine Adverse Event Reporting System, 593 TM cases following COVID-19 vaccination has been reported. This review highlights the potential mechanism, diagnosis, and management of COVID-19 vaccine-associated TM. Despite rare occurrences, it is imperative to overcome this vaccine hesitancy, occurring secondary to adverse events.